Updated definition of glass-ceramics - Deubener, J.; Allix, M.; Davis, M.J.; Duran, A.; Höche, T.; Honma, T.; Komatsu, T.; Krüger, S.; Mitra, I.; Müller, R.; Nakane, S.; Pascual, M.J.; et al. (Journal of non-crystalline solids, 2018)
Glass-ceramics are noted for their unusual combination of properties and manifold commercialized products for consumer and specialized markets. Evolution of novel glass and ceramic processing routes, a plethora of new compositions, and unique exotic nano- and microstructures over the past 60 years led us to review the definition of glass-ceramics. Well-established and emerging processing methods, such as co-firing, additive manufacturing, and laser patterning are analyzed concerning the core requirements of processing glass-ceramics and the performance of the final products. In this communication, we propose a revised, updated definition of glass-ceramics, which reads “Glass-ceramics are inorganic, non-metallic materials prepared by controlled crystallization of glasses via different processing methods. They contain at least one type of functional crystalline phase and a residual glass. The volume fraction crystallized may vary from ppm to almost 100%”. •An updated definition of glass-ceramics (GCs) is provided.•GCs are prepared by controlled crystallization of glasses via different processing methods.•GCs contain at least one type of functional crystalline phase and a residual glass.•The volume fraction crystallized of a GC may vary from ppm to almost 100%.